Boiled yam end-user preferences and implications for trait evaluation - Honfozo, Laurenda; Adinsi, Laurent; Bouniol, Alexandre; ADETONAH, Sounkoura; Forsythe, Lora; Kleih, Ulrich; HOUNHOUIGAN, DJIDJOHO JOSEPH; AKISSOE, H. NOËL (My University, 2020)
This study aimed to establish the quality characteristics of raw and boiled yam by involving stakeholders along the food chain using a methodology that includes a state of knowledge eview, focus group discussion and individual interviews, participatory processing diagnosis with processors and consumer testing. Predictive characteristics of yam for producing a high- and low-quality boiled yam were related to morphological or physicochemical characteristics: peeled yam discoloration and mucilage content being negatively appreciated while the ease of peeling, viscous state of cooking water and the ease of breaking yam into pieces positively valued. High-quality boiled yam should be white or yellowish, sticky to the fingers, nonfibrous, easy to chew, crumbly/friable, with a sweet taste and a good smell. The overall liking of boiled yam is greatly penalised by a too dark colour, hard to the touch, no sweet taste and no friability while eating.
Keywords: Check all that apply; consumer testing; gender; just about right; quality characteristics; sensory descriptors; survey